Expression of inducible nitric oxide synthase and its involvement in pulmonary granulomatous inflammation in rats. - Setoguchi, K. (1996)
Two types of pulmonary granulomatosis were produced in rats by intratracheal instillation of zymosan or silica. In both models, immunostaining with anti-rat monoclonal antibody for inducible nitric oxide synthase (iNOS), ANOS11, showed that the intensity of iNOS immunoreactivity in the inflammatory lesions peaked at 3 days and declined thereafter. Immunohistochemical double staining and in situ hybridization demonstrated the expression of iNOS in neutrophils, monocyte-derived macrophages, and bronchiolar epithelial cells in the pulmonary lesions. Electron spin resonance spectroscopy revealed the production of an excessive amount of nitric oxide (NO) in the pulmonary lesions. Immunostaining with a polyclonal antibody against nitrotyrosine indicated the formation of nitrotyrosine residues in the granulomatous lesions, particularly in the periphery of the lesions, providing indirect evidence for the generation of peroxynitrite anion in the zymosan- or silica-instilled lungs. Administration of N omega-nitro-L-arginine methyl ester or S-methylisothiourea sulfate, which significantly suppressed NO production, resulted in marked reduction of monocyte/macrophage infiltration as well as in inhibition of induction of monocyte chemoattractant protein-1 in the lesions. These data indicate that NO and its more reactive product peroxynitrite anion may be important mediators of granuloma formation in the lung.